Chemerin level in a sample of Egyptian females with PCOS and its relation to insulin resistance - Mohamed Reda Halawa; Rania Said Abd El Baky; Yara Mohamed Eid; Merhan Samy Nasr; Bahaa Mahmoud Taha; Laila Mahmoud Ali Hendawy (SpringerOpen, 2020)
Abstract Background Chemerin a novel adipokine is linked to insulin resistance and adiposity which are major characteristics of polycystic ovary syndrome (PCOS). Results Chemerin level was found to be significantly higher in PCOS group than in control group (94.99 ± 12.52 ng/dl vs 73.41 ± 6.95 ng/dl) (P < 0.001) being the highest in obese PCO group, also chemerin positively correlated with BMI, fasting insulin, and HOMA-IR (P < 0.001), Multivariate linear regression analysis for factors affecting chemerin level in both PCO groups showed that the most important factor was fasting insulin (P = 0.042). Conclusion Chemerin correlates with insulin resistance and may be involved in the pathogenesis of insulin resistance in PCOS patients.